A Comparison of Two Case Studies Using the Roy Adaptation Model: Parents of Opioid-Dependent Adults and Bariatric Surgery. (January 2019) - Russo, Sandra; Baumann, Steven L.; Velasco-Whetsell, Martha; Roy, Callista
The authors in this paper demonstrate the utility and versatility of the Roy Adaptation Model (RAM) as applied to two contemporary case studies. The first case uses the RAM model to gain understanding and guide nursing practice to assist the parents of a young adult with an opioid use disorder and depression, and the second case involves using the RAM model to help a woman who recently had bariatric surgery cope and adapt postoperatively in a way that helps her maximize the benefits of having had that procedure. The authors discuss how the RAM provides a holistic approach that can be used to provide high-quality, comprehensive nursing.